2023
DOI: 10.2478/ebtj-2023-0006
|View full text |Cite
|
Sign up to set email alerts
|

Structure of PAP-IgM FcK fusion protein with J-chain expressed in transgenic plant

Abstract: Transgenic plants expressing immunoglobulin (Ig) M Fc-fused Prostate acid phosphatase (PAP) antigenic proteins (PAP-IgM FcK) and J-chain proteins were generated by Agrobacterium-mediated transformation. The Fc region was tagged with the ER retention motif (KDEL) to make PAP-IgM FcK. Two transgenic plants were crossed together to generate F1 expressing both PAP-IgM FcK and J-chain proteins (PAP-IgM FcK × J-chain). PCR and RT-PCR analyses confirmed the transgene insertion and mRNA transcription of PAP-IgM FcK an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Recent studies on recombinant proteins that utilize the Fc region of IgM have shown that the majority of these proteins predominantly exist in a mixed state, comprised of both monomers and oligomers. [60][61][62] All subsequent experiments in this study were carried out using this mixed form of ACE2 μK without any further fractionation. ACE2 μK and ACE2 K were confirmed to bind with all five investigated SARS-CoV-2 RBD variants, although there were differences in the degree of binding.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on recombinant proteins that utilize the Fc region of IgM have shown that the majority of these proteins predominantly exist in a mixed state, comprised of both monomers and oligomers. [60][61][62] All subsequent experiments in this study were carried out using this mixed form of ACE2 μK without any further fractionation. ACE2 μK and ACE2 K were confirmed to bind with all five investigated SARS-CoV-2 RBD variants, although there were differences in the degree of binding.…”
Section: Discussionmentioning
confidence: 99%
“…2022; Kang et al . 2023). A 1 μL volume of each immunized and non‐immunized hemolymph was mixed with 19 μL of 1× PBS and 4 μL of a loading buffer (5% 2‐mercaptoethanol, 50% glycerol, 100 mM Tris–HCl, 10% SDS and 0.1% bromophenol blue) and loaded onto a 12% SDS‐PAGE gel.…”
Section: Methodsmentioning
confidence: 99%
“…SDS-PAGE was conducted to confirm the induction of attacins in immunized pupae, as described in previous report (Ko et al 1999;Lim et al 2022;Kang et al 2023). A 1 μL volume of each immunized and non-immunized hemolymph was mixed with 19 μL of 1× PBS and 4 μL of a loading buffer (5% 2-mercaptoethanol, 50% glycerol, 100 mM Tris-HCl, 10% SDS and 0.1% bromophenol blue) and loaded onto a 12% SDS-PAGE gel.…”
Section: Sodium Dodecyl Sulfate Polyacrylamide Gel Electrophoresis (S...mentioning
confidence: 99%
“…Plants are considered a heterologous bio-system for the production of valuable recombinant immunotherapeutic antibody proteins as an alternative to mammalian cell-based systems 5 . In plant expression system, the recombinant antibody genes are controlled by the CaMV35S promoter, which is considered a consistent and non-tissue-specific promoter in plant leaf and is mainly used for its stable or transient expression 6 8 . The transgene expression by the cauliflower mosaic virus (CaMV) 35S promoter has been investigated in leaf, root, and stem tissues 9 .…”
Section: Backgrounds and Summarymentioning
confidence: 99%